Solvothermal synthesis of nickel-based metal-organic framework (Ni-MOF) and its derivative for advanced symmetric supercapacitor applications - Zheng, Sheng Qiang (2024)
Nanomaterials have successfully attracted enormous interest in energy storage systems, such as batteries and supercapacitors (SCs), by virtue of the enhanced electronic and ionic conductivity as compared to traditional electrochemical energy storage materials. Meanwhile, small-sized materials are favorable for improving electrolyte ion diffusion and specific capacity due to the possibility of occupying all available sites in the particle volume. Among a wide range of electrode materials, high-crystalline conductive materials (such as nickel-based metal-organic frameworks (Ni-MOFs)), have been utilized as promising electrode active materials for SCs on the strength of their high porosities, ultra-large specific surface areas and structural tunability. More significantly, these materials are not only able to be utilized as electrode active materials, but also function as precursors to synthesize transition metal oxides and carbonaceous nanomaterials for energy storage systems. Nevertheless, there are still some challenges associated in the application of Ni-MOFs in high-performance SCs, such as inferior electrical conductivity, low energy density and durability. Hence, tremendous efforts have been made to study novel MOF-based nanostructures with enhanced electrochemical performance for their widespread implementation.